The Optional Regime of the Exemptions of the Administrative Procedures of Selection of Contractors - Linares Jara, Mario Ernesto (2015)
This article aims to determine the extent for the regimen of administrative procedure of selection, in the framework of the Peruvian Public Procurement Law. In that way, by analyzing the juridical doctrine and the Supervisory Agency of Public Procurement’s pronouncements on the matter, it will be determined that we are facing and optional regime on exemptions.